Contact lenses for visual rehabilitation in Bilateral Nanophthalmos with Retinal Dystrophy- A case report - Pradhan, Asik; Bhandari, Sanjeeb; Dhungana, Purushottam; Kaiti, Raju (Nepalese Journal of Ophthalmology, 2017)
Background: Nanophthalmos is an uncommon developmental ocular disorder characterized by a small eye with short axial length, high hyperopia and high lens to eye volume ratio due to arrested development of the globe in all directions. Different types of fundus changes can rarely occur with nanophthalmos. Observations: This is a case report of a 17 years old female who presented with bilateral gradual progressive visual loss and photophobia at Tilganga Institute of Ophthalmology on 3rd July 2015. Her best corrected visual acuity was 20/300 with +12.00Ds/-1.00Dcyl@180 in the right eye and 20/200 with +12.00Ds/-1.50Dcyl@180 in the left eye. Axial lengths of two eyes were markedly shortened with pigmentary changes at the macula and dull foveal reflex along with retinal flecks in the mid-periphery. Full field ERG showed diminished rod and cone waves suggestive of rod and cone dysfunction. With the use of Rigid Gas Permeable (RGP) contact lenses, the acuity improved to 20/200 and 20/125 in the right and left eye respectively. Conclusion: This study proposes the use of contact lenses and light absorptive filters for better visual rehabilitation.